Non-invasive estimation of muscle fiber type composition in swimmers - Bex, T.; Baguet, A.; Derave, W. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Aim Excellence in sports with short and long exercise duration requires a high proportion of fast (FT) and slow twitch (ST) muscle fibers, respectively. Based on the positive correlation between the carnosine concentration and the percentage area of FT fibers in skeletal muscle, proton magnetic resonance spectroscopy (1H-MRS) has been proposed as a non-invasive method to estimate muscle fiber type composition (MFTC) (Baguet et al, 2011). In athletics, there is a strong relationship between estimated MFTC and optimal running distance (Baguet et al., 2011), but it is unclear whether this also applies to swimming. The aim of this study is to explore estimated MFTC in swimmers, excelling at various distances. Methods: Eleven Belgian elite swimmers and 10 control subjects were recruited to measure muscle carnosine content in soleus, gastrocnemius and deltoid muscles by 1H-MRS. They were divided in 3 groups (short, middle and long distance) based on their best swimming distance. Results: The long distance swimmers had the lowest relative carnosine concentration in the leg (soleus + gastrocnemius) muscle compared with middle (p = 0.011) and short ( p = 0.001) distance swimmers (0.126, 0.180 and 0.213, respectively). In the deltoid muscle, the long distance swimmers had a significant lower carnosine concentration and the middle distance swimmers had a tendency to lower carnosine concentration than the short distance group (0.071 and 0.095 vs. 0.133). The total group of swimmers had a lower relative concentration in the deltoid muscle compared to the control group (p = 0.004), but for the gastrocnemius muscle no significant differences were found (p = 0.442). Conclusions In all measured muscles, differences were found between the three distance groups of swimmers, which indicates that the relationship between MFTC and optimal distance and exercise duration also applies to swimming. The lower baseline carnosine concentration in deltoid muscle from swimmers could suggest a long-term transition from type II to type I muscle fibers, which is probably caused by chronic aerobic training of the upper body, which does not occur in the controls. So this new method may have useful applications in talent identification and discipline (re)orientation in all MFTC-dependent sports.